Sex differences in morphological dimensions in twelve-year-old children from Imotska Krajina - Gudelj Ceković, Ines; Milat, Sanja; Retelj, Edvard; Zagorac, Nebojša; Ljubičić, Mate, liječnik; Katić, Ratko (2009)
Abstract: The aim of the study was to identify and compare morphological characteristics of 12-year-old male and female children from Imotska krajina. The structure of a set of 23 morphological space variables were determined in a sample of 75 male and 67 female children by use of factor analysis for each sex in separate. Factor structure showed two basic superior latent dimensions responsible for directly measurable manifestations of morphological parameters in both male and female children. One of these two dimensions behaved as a general mechanism of growth and development, whereas the other showed a bipolar pattern. Bipolarity was almost exclusively determined by adipose tissue on one pole, and by skeletal longitudinal growth on the opposite pole.
Rotation of the main components to varimax position yielded two morphological dimensions that were well balanced in both sexes (slightly better in girls); besides the predominant increase in adipose tissue, one of these dimensions was also responsible for the development of muscular tissue and skeletal transverse development, whereas the other was responsible for skeletal transverse development and muscular tissue development in addition to the predominant longitudinal skeletal growth. These observations suggested two developmental processes, i.e. transverse morphological development (first factor) and longitudinal morphological development (second factor), to be almost equally involved in the morphological development of 12-year-old male and female children. These developmental processes are highly genetically determined and can only in part be explained by the intensity of kinesiologic engagement.
Based on the morphological structures defined, discriminative function of the morphological space primarily differentiated two developmental processes, i.e. longitudinal skeletal development (hand length in particular) in female children relative to transverse skeletal development (knee diameter in particular) in male children, pointing to the presence of full-swing puberty in female children, while yet to be expected in male children; thereafter, the differences in the ectomesomorphic morphological characteristics would be by far more pronounced in favor of male children
Bibliografija: 30 jed
Sažetak
Keywords: Spolne razlike -- Morfološke karakteristike -- Pubertet -- Dvanaestogodišnjaci; Imotska krajina